The Relationship between Professional Ethics of University Professors and Job Satisfaction and Self-Efficacy Beliefs (Case Study of Karaj University Professors) - Roya Aghaie motlagh (Institute of Management fekrenoandish, 2021)
The aim of this study was to determine the relationship between professional ethics of university professors and their job satisfaction and self-efficacy beliefs. This study was a correlational study. The statistical population of this study included all full-time faculty members of the Islamic Azad University, Karaj Branch in the academic year 2018-2019, 120 individuals. Based on Morgan table, a sample of 92 persons was determined and selected by available sampling method. Data collection tools were Riggs & Knight (1994) General Self-Efficacy Scale, Cadozier Professional Ethics Scale (2002), and Job Satisfaction Questionnaire by Abu Bakr et al. (2017). Data analysis using Pearson correlation coefficient method showed that there is a relationship between professional ethics of university professors and their job satisfaction and self-efficacy beliefs (P <0.05). There is also a relationship between the dimensions of professional ethics of university professors with their job satisfaction and self-efficacy beliefs (P <0.05). Based on these findings, it is advisable to the professors to use their efforts to establish an ethical job environment in order to develop their abilities and achieve job satisfaction.